The role of data management in the Industrial Internet of Things. (25th September 2020) - AlSuwaidan, Lulwah
Summary: The rapid development of Internet technology, networking, and emergence technologies has deeply impacted manufacturing. Moreover, the massive data being generated have increased tremendously. All of these factors have supported the transformation of the traditional manufacturing paradigm toward smart manufacturing. At present, the Industrial Internet of Things (IIoT) is an underlying platform for various smart manufacturers seeking an effective and powerful structure. Oil and gas is an industry affected by this transformation. This article discusses the role of data management in supporting the IIoT and smart manufacturing. It also proposes a taxonomy that classifies and categorizes the pillars of data management in the IIoT. It includes the basis of important parameters such as data sources, machine learning, performance management, business intelligent, and big data. In order to measure the role of data management in the IIoT, we consider Saudi Arabia as a case study for the IIoT, and review and explore the current challenges and potential future solutions. In addition, we propose an Internet of Things (IoT)‐based reliable architecture for monitoring the flow of operations in the oil and gas industry.